The Relationship Between Self-Stigma and Subjective Well-Being in Tuberculosis Patients - Dwi Megawati; Ainul Yaqin Salam; Rizka Yunita (Health and Technology Journal (HTechJ), 2024)
Pulmonary tuberculosis (TB) sufferers often face psychosocial problems in the form of stigma. Stigma contributes to psychological morbidity. Morbidity impacts psychological well-being. This research aims to determine the relationship between stigma and subjective well-being in tuberculosis at the Klakah Community Health Center, Lumajang Regency. This study is correlative research with a cross-sectional approach. The population in this study was Tuberculosis Patients at the Klakah Lumajang Community Health Center in 2024. The sample was adjusted based on the Slovin formula to 37 respondents. The side technique used is purposive sampling. Data was collected using the validated The Van Rie tuberculosis stigma scale and The BBC subjective well-being scale questionnaires. Data analysis in this study used Spearman Rho. The results showed that almost half of tuberculosis patients had a high level of Self-Stigma (45.9%), almost half of them had a low level of subjective well-being (43.2%). Data analysis shows that there is a significant relationship between Self-Stigma and subjective well-being in tuberculosis patients (p-value = 0.000; α = 0.05; r = -0.874) which shows a relationship with a strong negative correlation level which means that self- Low stigma will have implications for increasing subjective well-being. The psychosocial health issue of stigma appears to be one of the most important issues that must be addressed to avoid its enormous and negative impact on health promotion.